2016
DOI: 10.1080/14719037.2016.1148192
|View full text |Cite
|
Sign up to set email alerts
|

Assessing public leadership styles for innovation: a comparison of Copenhagen, Rotterdam and Barcelona

Abstract: This article explores which leadership qualities public managers regard as important for public innovation. It is based on a survey of 365 senior public managers in Copenhagen, Rotterdam and Barcelona. Five perspectives on leadership were identified and tested using a number of items. Some of these proved to be more robust than others. Analysis of the three cities reveals a nuanced set of leadership styles, which include a transformational style, and one that is more dedicated to motivating employees, risk-tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 33 publications
2
54
0
9
Order By: Relevance
“…Frequently, more rules, controls, and constraints that limit the acceptable behavior of civil servants, rather than innovation, are considered to be a remedy in the case of performance deficiencies ( Kelman 2008 ). However, public organizations must change frequently because of shifts in public policy and priorities (Ricard et al 2017). Innovative practices can help public sector organizations address changes and stakeholder expectations and provide legitimacy for the government as an institution that creates public value ( Moore 2014 ).…”
Section: Innovative Behavior In Public Sector Organizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently, more rules, controls, and constraints that limit the acceptable behavior of civil servants, rather than innovation, are considered to be a remedy in the case of performance deficiencies ( Kelman 2008 ). However, public organizations must change frequently because of shifts in public policy and priorities (Ricard et al 2017). Innovative practices can help public sector organizations address changes and stakeholder expectations and provide legitimacy for the government as an institution that creates public value ( Moore 2014 ).…”
Section: Innovative Behavior In Public Sector Organizationsmentioning
confidence: 99%
“…Fernandez and Rainey (2006 ) emphasized that management practices are important for employee acceptance of change. Despite some evidence that entrepreneurial leadership may be effective in promoting innovative outcomes in the public sector (Ricard et al 2017), there is limited knowledge of the underlying psychological processes that link entrepreneurial leadership with the innovative behavior of individual employees.…”
Section: Entrepreneurial Leadership and Innovative Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Yoon (2015) mentioned that transactional leadership is still important to accelerate cultural change in organizations. On the other hand, transformational leadership styles, and styles that are more dedicated to motivating employees, taking risks and including others in decision making are also considered important by public personnel (Ricard, Klijn, Lewis, & Ysa, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The public sector and public leadership both are dynamic fields (Van Wart, ). Ricard, Klijn, Lewis, and Ysa () conducted research on the managers of three cities to assess the different public leadership styles and their impact on decision making. Ricard et al found that public leadership is influenced by transformational leadership to a great extent.…”
Section: Introductionmentioning
confidence: 99%